Comparison of Propofol Versus Propofol with Low Dose Scoline To Evaluate LMA Insertion (Indian Journal of Applied-Basic Medical Sciences, 2021)
BACKGROUND: The laryngeal mask airway (LMA) is an innovative device made for upper airway management and its use is well established in anaesthesia practice. It enables the anaesthesiologist to keep both hands free and obviates the need for tracheal intubation. Moreover, it does not cross the glottic opening, so the hazards of laryngoscopy and tracheal intubation are avoided in patients especially going for short duration surgeries (1). It can be inserted with or without aid of neuromuscular blockade but the level of anaesthesia should be sufficient to abolish gag reflex and jaw relaxation. OBJECTIVES: A prospective, observational study of propofol versus propofol with low dose scoline to evaluate LMA insertion was undertaken with the aims of comparison of two groups for different variables like ease of insertion, number of attempts, hemodynamic changes at the time of insertion, use of rescue drug needed for LMA insertion and incidence of complications (at the time of LMA insertion and postoperatively) METHODS: The study was done in 60 adult (15 to 50 years of age) patients with ASA grade 1 and 2 who were undergoing planned elective surgery under general anaesthesia with spontaneous breathing. Out of 60 patients two groups were made, 30 patients in group P and 30 patients in group P+S.Among them, Group P received Inj. Propofol 2.5 mg/kg and 5 ml sodium chloride (0.9%) I.V. bolus after 30 seconds and Group P+S received Inj. Propofol 2.5 mg/kg + Inj. succinylcholine 0.1 mg/kg diluted in 5 ml sodium chloride (0.9%) I.V. Hemodynamic parameters, insertion variables and other data were noted. RESULTS: Hemodynamic parameters remained consistent in both the groups, with more stable pulse rate and MAP in group P+S. No patient had any complication like coughing, gagging or laryngospasm in any group at the time of LMA insertion CONCLUSION: Low dose scoline with propofol for LMA insertion reduces upper airway responses, lowers the requirement of rescue drug and also lowers the chances of apnoea and hypotension due to incremental doses of propofol.
Keywords: LMA; Propofol; Scoline